MIMICRY AS RESISTANCE OF POSTCOLONIAL SOCIETY IN KIRAN DESAIS THE INHERITANCE OF LOSS - ANDRIANI ASTUTIK, CICILIA (LANGUAGE HORIZON, 2019)
ABSTRACT Desai?s The Inheritance of Loss narrates a parallel story of post-colonial India and the United States, from Jemubhai Patel (the Judge), the Cook, and Biju (son of the Cook, an illegal immigrant in New York). Like the other postcolonial fiction, themes like identity crisis, western-centrism, class social and others are adhered in it, but this research sees something that behind these all themes, there is resistance. Therefore, this research proposes problem of how the Indian characters are described in Desai?s The Inheritance of Loss and what resistances that they expose in Desai?s The Inheritance of Loss. To accommodate it, this research uses Bhabha?s theory of Third Space to propose the deconstructive resistance in the crisis of identity. The method uses critical interpretation as data analysis. The results show that behind the identity crisis in Jemubhai (a man with hatred of Indian culture) and Biju (a boy who thinks West is better), there is something deconstructive to see that they try to be unidentified as eastern who is under colonial discourse, such as poor, local, uncivilized, traditional, and non-globalized people. Key Terms: Postcolonial, Identity, Third Space, and Resistance